2010
DOI: 10.1371/journal.ppat.1001015
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir-Resistant Pandemic A/H1N1 Virus Is as Virulent as Its Wild-Type Counterpart in Mice and Ferrets

Abstract: The neuraminidase inhibitor oseltamivir is currently used for treatment of patients infected with the pandemic A/H1N1 (pH1N1) influenza virus, although drug-resistant mutants can emerge rapidly and possibly be transmitted. We describe the characteristics of a pair of oseltamivir-resistant and oseltamivir-susceptible pH1N1 clinical isolates that differed by a single change (H274Y) in the neuraminidase protein. Viral fitness of pH1N1 isolates was assessed in vitro by determining replication kinetics in MDCK α2,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 40 publications
(56 reference statements)
8
89
2
1
Order By: Relevance
“…Interestingly, our group and other investigators reported that A(H1N1)pdm09 H275Y variants conserved a good fitness and exhibited efficient contact transmission when assessed in ferrets and guinea pigs (Hamelin et al, 2010;Memoli et al, 2011;Seibert et al, 2010;Wong et al, 2012). Furthermore, we previously demonstrated that the A(H1N1)pdm09 H275Y mutant was at least as virulent as the WT virus in BALB/c (Hamelin et al, 2010) and C57BL/6 mice. At this time, little information is available regarding the fitness and virulence of zanamivir-resistant A(H1N1)pdm09 viruses.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, our group and other investigators reported that A(H1N1)pdm09 H275Y variants conserved a good fitness and exhibited efficient contact transmission when assessed in ferrets and guinea pigs (Hamelin et al, 2010;Memoli et al, 2011;Seibert et al, 2010;Wong et al, 2012). Furthermore, we previously demonstrated that the A(H1N1)pdm09 H275Y mutant was at least as virulent as the WT virus in BALB/c (Hamelin et al, 2010) and C57BL/6 mice. At this time, little information is available regarding the fitness and virulence of zanamivir-resistant A(H1N1)pdm09 viruses.…”
Section: Discussionmentioning
confidence: 61%
“…Such variants are also resistant to peramivir but retain susceptibility to zanamivir and laninamivir (Pizzorno et al, 2011;Samson et al, 2014). Interestingly, our group and other investigators reported that A(H1N1)pdm09 H275Y variants conserved a good fitness and exhibited efficient contact transmission when assessed in ferrets and guinea pigs (Hamelin et al, 2010;Memoli et al, 2011;Seibert et al, 2010;Wong et al, 2012). Furthermore, we previously demonstrated that the A(H1N1)pdm09 H275Y mutant was at least as virulent as the WT virus in BALB/c (Hamelin et al, 2010) and C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 74%
“…Unlike the growth of pre-2007 seasonal H1N1 strains, that of the H1N1pdm09 H275Y MUT (H1N1pdm09-MUT) strain is not severely compromised in vitro or in ferrets (9,12,15,31). Contact transmissions of H1N1pdm09-MUT between ferrets have been successful in all of the experiments reported (15,16,35,38,45).…”
mentioning
confidence: 97%
“…[6][7][8] In addition, by using specific primers and probes, the different subtypes of influenza A can be discriminated. [6][7][8][9][10] However, current PCR methods continue to rely heavily on slab gel electrophoresis (SGE) analysis, which requires several hours to obtain results and is extremely low-throughput, making this technique unsuitable for a large number of samples. 11 Even though real-time PCR (RT-PCR) methods may decrease analysis time, they require special thermo-cyclers equipped with an expensive and sensitive camera and well-designed primers.…”
Section: Introductionmentioning
confidence: 99%